Developing an internet of things system for hydrogen leak detection at hydrogen refueling stations integrating LoRa and global positioning system - Hwang, Ha-Jin; Hwang, Sung-Ho (Edelweiss Applied Science and Technology, 2024)
Developing a hydrogen leak detection system that can quickly detect even the smallest amount of hydrogen is extremely crucial in the hydrogen industry. Currently, hydrogen refueling stations use a fixed hydrogen leak detection system. This study develops a mobile hydrogen gas leak detection system for hydrogen refueling stations using s, global positioning system, and Internet of Things (IoT) equipment, including LoRa and Wi-Fi. A digital twin is implemented by linking hydrogen gas-sensing data at a location that is quickly required or suspected using Google Maps. A time-series database is used to store the hydrogen gas-sensing data, and the transfer delay of hydrogen gas-sensing data between the hydrogen equipment was measured. Therefore, we developed a prototype system that transmits, stores, and analyzes hydrogen gas-sensing data in real time using IoT equipment for hydrogen refueling stations.